FPGA Hardware Realization: Addition of Two Digital Signals Based on Walsh Transforms - Zulfikar Zulfikar; Shuja A Abbasi; Abdul Rahman M Alamoud (Institute of Advanced Engineering and Science, 2016)
This paper presents hardware realization of addition of two digital signals based on Walsh transforms and inverse Walsh transforms targeted to the Xilinx FPGA Spartan 3 board. The realization utilizes Walsh Transform to convert the input data to frequency domain and the inverse Walsh transform to reconvert the data from frequency domain. The designed system is capable of performing addition, subtraction, multiplication and Arbitrary Waveform Generation (AWG). However, in the present work, the hardware realization of addition only has been demonstrated. The Clock frequency for realization into the board is supplied by an external function generator. Output results are captured using a logic analyzer. Input data to the board (system) is passed manually through the available slide switches on-board.